Congenital adrenal hyperplasia and vanishing testis: rare case of male pseudohermaphroditism - Azam Ghanei; Golnaz Mohammadzade; Ehsan Zarepur; sedighe soheilikhah (Iranian Journal of Reproductive Medicine, 2016)
Background: Congenital adrenal hyperplasia (CAH) and vanishing testes are uncommon diseases that can result from hormonal and mechanical factors. Classic CAH is determined by ambiguous genitalia and increase in amount of 17-Hydroxyprogesterone. Simultaneous occurrence of CAH and vanishing testes is a rare condition. Case: A 22-year-old boy, known case of CAH who was diagnosed as female pseudohermaphroditism due to ambiguous genitalia, was referred to Shahid Sadoughi Hospital, Yazd, Iran with colicky abdominal pain and hematuria. Ultrasonography has been performed and prostate tissue was reported. Karyotyping was done because of uncertainty in primary diagnosis, which revealed 46XY. For finding location of testes, ultrasonography and MRI were done and nothing was found in abdomen, inguinal canal or scrotum. Inhibin B serum level was measured to find out whether testis tissue was present in the body, which was <1 pg/ml and vanishing testis was confirmed. Conclusion: Early diagnosis and treatment are essential to prevent further sequels and karyotyping for all patients with CAH is recommended. Lifelong treatment with synthetic glucocorticoid replacement is necessary